2020
DOI: 10.1186/s12913-020-05498-7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with health care and health-related quality of life of patients with hematologic malignancies in Mexico

Abstract: Background In Mexico, patients with hematologic malignancies (HMs) are characterized by being at high risk and advanced stages at diagnosis and by having a low cure rate; yet information on their experiences with health care and health-related quality of life (HRQL) is scarce. We aimed to evaluate experiences with health care and HRQL of patients with HMs and the association between these patient-reported measures. Methods We conducted a cross-sectional survey in two pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…In this study, we evaluated the emotional issues using multiple tools and suggested that emotional upsets such as depression, anxiety, and stress were surprisingly common in Chinese CLL patients. The proportion of depression and anxiety was much higher than other reports of CLL and lymphoma [19,20]. However, there was no signi cant difference between "watch and wait" patients and active treatment patients regarding emotional upsets.…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, we evaluated the emotional issues using multiple tools and suggested that emotional upsets such as depression, anxiety, and stress were surprisingly common in Chinese CLL patients. The proportion of depression and anxiety was much higher than other reports of CLL and lymphoma [19,20]. However, there was no signi cant difference between "watch and wait" patients and active treatment patients regarding emotional upsets.…”
Section: Discussioncontrasting
confidence: 61%
“…Additionally, illness uncertainty was related to more negative emotions (Cui et al, 2020); this may have a negative effect on QoL. Receiving clear information on disease and therapy has been reported to be associated with better QoL (Doubova et al, 2020). Our findings provide evidence that illness uncertainty should be recognised as an important factor to improve QoL in patients with CML.…”
Section: Discussionmentioning
confidence: 99%
“…Meeting the needs of the opposite sex can lead to a decrease in tension while hindering the satisfaction of the opposite sex's needs can lead to an increase in pressure. Music that conforms to psychological inertia gives people a natural and smooth feeling, while conversely, it makes people feel sudden and tense (Doubova et al, 2020). For example, in situations where interval congruence is similar, jumping in at large intervals is more stressful than progressing at small intervals because it does not meet the requirements of customary expectations.…”
Section: Psychological Level Of Expectationmentioning
confidence: 99%